1998
DOI: 10.1002/(sici)1098-1136(199808)23:4<349::aid-glia7>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic regulation of Na+/K+-ATPase transport activity in the RN22 Schwann cell line in response to stimulation of cyclic AMP production

Abstract: Na+/K+‐ATPase‐dependent Rb+ uptake of RN22 Schwann cells was stimulated by cholera toxin (0.25 μg/ml), forskolin (2 mM), or 8‐bromo cAMP (1 mM). At 2 h Rb+ uptake was increased by 162 ± 6% (cholera toxin), 151 ± 14% (forskolin), and 207 ± 15% (8‐bromo cAMP). Cholera toxin or 8‐bromo cAMP treatment for 12–24 h resulted in a second peak of Na+/K+‐ATPase‐dependent Rb+ transport activity of 186 ± 12 and 265 ± 9% of control, respectively. Cholera toxin also transiently stimulated the activity of the Na+, K+, 2Cl−‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Although direct phosphorylation of the Na ϩ -K ϩ -ATPase appears to correlate with the well-documented PKA-mediated stimulation of enzyme phosphorylation and ouabain-sensitive 86 Rb ϩ uptake in renal proximal tubules (63), there is evidence to support the notion that the activation is secondary to an increase in plasma membrane pumps (64). Perhaps related to this are the observed PKA-induced increases in plasma membrane pumps of MDCK (323) and Schwann cells (312). Although direct phosphorylation of the Na ϩ -K ϩ -ATPase by PKA is an attractive simple mechanism for PKA-mediated regulation of the enzyme and appears to apply to at least some systems, other more complex mechanisms have been observed.…”
Section: Signaling Events Involved In Hormone Actionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although direct phosphorylation of the Na ϩ -K ϩ -ATPase appears to correlate with the well-documented PKA-mediated stimulation of enzyme phosphorylation and ouabain-sensitive 86 Rb ϩ uptake in renal proximal tubules (63), there is evidence to support the notion that the activation is secondary to an increase in plasma membrane pumps (64). Perhaps related to this are the observed PKA-induced increases in plasma membrane pumps of MDCK (323) and Schwann cells (312). Although direct phosphorylation of the Na ϩ -K ϩ -ATPase by PKA is an attractive simple mechanism for PKA-mediated regulation of the enzyme and appears to apply to at least some systems, other more complex mechanisms have been observed.…”
Section: Signaling Events Involved In Hormone Actionmentioning
confidence: 97%
“…Cantiello (61) showed that phosphorylation of monomeric actin by PKA prevented the actin-mediated stimulation of the sodium pump, whereas phosphorylation of polymeric actin promoted it. Finally, in some cases, PKA does not regulate the sodium pump directly but, rather, alters the function of other Na ϩ transporters, leading to changes in cytoplasmic Na ϩ concentration, which in turn alter Na ϩ -K ϩ -ATPase activity (164,312).…”
Section: Signaling Events Involved In Hormone Actionmentioning
confidence: 99%